2016
DOI: 10.1093/jae/ejw020
|View full text |Cite
|
Sign up to set email alerts
|

Youth Unemployment and Earnings in Africa: Evidence from Tanzanian Retrospective Data

Abstract: We exploit a unique dataset of individual labour market histories in urban Tanzania to estimate the effect of early labour market experiences on adult labour market outcomes. We consider four labour market entry stateswage employment, selfemployment, unpaid worker in the family business, and unemployed job-seekerand estimate how final earnings are associated with each entry state. The findings suggest that how individuals enter the labour market does matter for final earnings.We find that an initial period spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Some move straight into apprenticeships and similar arrangements, but others do not. Evidence from urban Tanzania (Bridges et al 2013) shows that some young people do odd jobs and are supported by their families for as long as fi ve years before they settle into wage jobs or (mostly) self-employment. Moreover, fi rst-generation school leavers aspiring to be wage workers lack a family history in formal employment.…”
Section: Figure O4 Informal Will Be Normal In 2020mentioning
confidence: 99%
“…Some move straight into apprenticeships and similar arrangements, but others do not. Evidence from urban Tanzania (Bridges et al 2013) shows that some young people do odd jobs and are supported by their families for as long as fi ve years before they settle into wage jobs or (mostly) self-employment. Moreover, fi rst-generation school leavers aspiring to be wage workers lack a family history in formal employment.…”
Section: Figure O4 Informal Will Be Normal In 2020mentioning
confidence: 99%
“…Other analysis finds a high premium (up to 50 percent) for wage jobs with a contract (often called formal wage jobs) (Rouband Torelli, 2013). Of course, these differences could reflect unmeasured and/or unobserved personal characteristics and not any type of segmentation (Bridges, et al, 2014).…”
Section: Matching and Mobility Between Sectorsmentioning
confidence: 99%
“…This is especially true for the HE sector. Some leave the wage sector to start a HE, but almost no one got to the wage sector from the HE sector after the age of 25 in urban Tanzania (Bridges et al 2014). In Ethiopia, panel data covering urban residents in a 10 year period from 1994-2004 showed that of those in self-employment in 1994 and still in the labor force in the final period, 2/3 were still in self employment, while only 10 percent had found a formal wage job.…”
Section: Matching and Mobility Between Sectorsmentioning
confidence: 99%
“…Tanzania has the highest average youth unemployment rate of 42 percent, well above Sub-Saharan Africa's average rate of 22.8 percent (Elder and Kone 2014). Joblessness in Tanzania is largely due to a lack of sufficient aggregate demand for labour relative to aggregate supplya problem that is particularly acute for young adults, and even more so for urban youth (Bridges et al 2005;Kondylis and Manacorda 2008;Garcia and Fares 2008;Restless Development 2013). Long-term is a serious problem: more than 40 percent of unemployed young adults in Tanzania have been unemployed for more than two years, and more than 70 percent have been unemployed for more than a year (Garcia and Fares 2008).…”
Section: Young People's Social and Economic Vulnerability In Uganda Amentioning
confidence: 99%